Intoxicating minds : how drugs work - Regan, Ciaran (Maps of the mind., 2001)
"Why do smokers claim that the first cigarette of the day is the best? What is the biological basis behind some heavy drinkers' belief that the "hair-of-the-dog" method alleviates the effects of a hangover? Why does marijuana seem to affect a person's problem-solving capacity? Intoxicating Minds is, in the author's words, "a grand excavation of drug myth." Neither extolling nor condemning drug use, it is a story of scientific and artistic achievement, war and greed, empires and religions, and includes lessons for the future." "Ciaran Regan looks at each class of drugs, describing the historical evolution of their use, explaining how they work within the brain's neurophysiology, and outlining the basic pharmacology of those substances."--Jacket